Investigation of airborne contaminant transmissions using network models: COVID-19 outbreak and potential risk in senior care facilities - Chul Kim; Yun Gyu Lee; Kichul Kim (Heliyon)
Many COVID-19 outbreaks occurred in senior care facilities during the last three years. Senior care facilities are nursing places for the long-term treatment and care of senior citizens, who are prone to be exposed to an infectious disease that spreads into these buildings. Therefore, this study investigated airborne contaminant transmissions based on outbreak cases in senior care facilities in Korea and analyzed the potential impact of architectural features in a selected senior care facility using network simulations. The results showed that during COVID-19 outbreaks in 85 senior care facilities the staff accounted for the largest proportion of the index cases, indicating that the staff members would be the primary virus carriers in the initial process of the virus transmission in the senior care facilities. Network simulations indicated that the (reverse) stack effect could significantly influence airborne contaminant transmission in these facilities during the summer and winter months. The indoor airborne contaminant exposure may change according to seasonal indoor airflows, with the potential for long-distance airborne contaminant transfer through shafts (e.g., elevators and staircases) in the senior care facility. The findings of this study can serve as a reference for developing customized countermeasures against airborne contaminant transmissions in senior care facilities.